The Impact of Effective Colour Management for Textile Coloration: An Instrumental Way Towards Perfection - Zeeshan Khatri; Ghulam Yasin Shaikh; Shaheen Aziz (Mehran University Research Journal of Engineering and Technology, 2011)
The colour produced by the application of either dyes or pigments on textiles must be close matched with reference (standard) provided by buyer. Meeting stringent requirement from Buyer that demands right colour on right time is not a simple task to achieve. The process of colour matching is a lengthy process and needs many trials to get close match. The colour quantification through instruments helps to cut most of the lead time, however, there is a serious need to manage colour during colour approval stage and coloration process. We adopted four different routes for colour approval and compared with the conventional one. The study revealed that out of four instrumental options, the 4th option had shortest route and minimum lead time. We also concluded that by using spectrophotometer, K/S (Colour Strength) and colorimetic values are very good to not only communicate colour numerically but also controlling colour during colour approval process.